CORRUPTION INTHE PUBLIC AND PRIVATE ORGANIZATION OF PAKISTAN: PERCEPTUAL VIEWS OF DISTRICT FAISALABAD, PUNJAB, PAKISTAN - Shahzad, Naeem; Naz, Tabssum; Shahid, Farhan; Usmani, Feroz; Khuram, Hafiza Rukhsana (The journal of contemporary issues in business and government, 2021)
Corruption has become a severe problem in Pakistan and it is shaking the foundation of the country. Corruption is equally problematic to measure and quantify. Therefore a comprehensive practice is to access the perception of corruption among people. This study evaluate situation, seriousness, causes and level of corruption. This study based on descriptive survey type’s research. It also measurements the awareness of corruption among people of Faisalabad. Majority of the people have personal experience of corruption.Most of people observe that the officials of political government are not demonstrating any political from public establishments. They observe the feeble accountability machinery is the major causes of corruption in government and Private departments.